A New Green CFIA/MZT System for Spectrophotometric Determination of Anthranilic Acid - Hussien, Jehan Sh.; Qassim, Bushra B. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Anthranilic acid (AA) was determined in pure material via a new system of the CFIA method that involves less chemical consumption (μL), is rapid, semiautomated, simple, and accurate. Two reactions of the AA were conducted; the first, with 4-amino antipyrine and potassium periodate as the oxidizing agent, yielded a pinkish-violet colored product, which was measured at λmax 550 nm. The second reaction, using 2,2`-bipyridine with FeCl3, produced a Pinkish-red product, which was measured at λmax 521 nm. Other chemical and physical factors that affect the stability of the complex products in the suggested process include flow rate, reagent concentration, sample volume, dispersion, and reaction coil. The linearity ranges were (10-400) and (5-150) µg.mL-1, the average recovery percentages were 100.995 and 100.974, while the error percentages were 0.995 and 0.974, respectively. The detection limit values were 1.63 and 0.69 μg.mL-1, respectively. A relative standard deviation of 0.28% and 0.65% was observed, and the sample throughput was 80 and 90 samples/hour, respectively. The devised approach was tested against the conventional method and was shown to be more sensitive. Moreover, a t-test was used to contrast "true value" with "practical value". At the 95% confidence level, it was found that the values were not significantly different.